Hubungan Pengetahuan Dan Kepatuhan Pola Hidup Sehat Pada Lansia Hipertensi Di Puskesmas Grogol Kabupaten Sukoharjo - Regita Athasya Eryani; Agus Sudaryanto (Jurnal Skala Kesehatan, 2026)
Hypertension is a major health problem among the elderly that requires a high level of adherence to a healthy lifestyle to prevent complications. This study aimed to analyze the relationship between the level of knowledge and adherence to a healthy lifestyle among elderly patients with hypertension at Grogol Public Health Center, Sukoharjo Regency. This study employed a quantitative correlational design with a cross-sectional approach. A total of 382 elderly patients with hypertension were selected as samples using an accidental sampling technique. Data were collected using questionnaires on knowledge and adherence to a healthy lifestyle and analyzed using the Spearman Rank correlation test. The results showed that most respondents had a moderate level of knowledge (45.0%) and a moderate level of adherence (46.1%). Statistical analysis revealed a very significant positive relationship between knowledge and adherence to a healthy lifestyle among elderly patients with hypertension (p = 0.000; r = 0.274). In conclusion, knowledge is an important determining factor in improving adherence to a healthy lifestyle among elderly patients as part of hypertension management.